2014
DOI: 10.1149/2.0071411eel
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolyzed Copper-Based Catalyst with High Oxygen Reduction Activity for PEM Fuel Cell Applications

Abstract: We have synthesized a copper-based catalyst for the oxygen reduction reaction in low temperature fuel cells. Catalysts were prepared by covalently attaching a phthalocyanine-type ligand to a carbon black surface, and adding Cu(OAc) 2 . The phthalocyanine-type ligand provides the nitrogen to form the presumed catalytic centers with the Cu metal. Rotating ring disk electrode experiments revealed that the catalytic activity of the as-synthesized material is greatly enhanced after one-step pyrolysis under inert at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…There is to our knowledge no example of direct chemical deposition of CuPc on low surface area, bare hydrophobic graphite via non-covalent interactions. Besides, the reported carbon-supported CuPc are either used as such, i.e., with no further transformation of the immobilized CuPc complex (Pakapongpan et al, 2014;Reis et al, 2014;Bian et al, 2020), or after pyrolysis at high temperatures to modify the carbon support (Ding et al, 2012;Goenaga et al, 2014). Their main applications are electrochemistry (Ding et al, 2012;Goenaga et al, 2014;Pakapongpan et al, 2014;Reis et al, 2014;Bian et al, 2020) and photocatalysis (Mukherjee et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…There is to our knowledge no example of direct chemical deposition of CuPc on low surface area, bare hydrophobic graphite via non-covalent interactions. Besides, the reported carbon-supported CuPc are either used as such, i.e., with no further transformation of the immobilized CuPc complex (Pakapongpan et al, 2014;Reis et al, 2014;Bian et al, 2020), or after pyrolysis at high temperatures to modify the carbon support (Ding et al, 2012;Goenaga et al, 2014). Their main applications are electrochemistry (Ding et al, 2012;Goenaga et al, 2014;Pakapongpan et al, 2014;Reis et al, 2014;Bian et al, 2020) and photocatalysis (Mukherjee et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…28,29,[32][33][34][35] It was demonstrated that the morphology and therefore the electrocatalytic properties of Cu nanostructures towards the CO 2 RR can be tuned by the addition of phosphate and the electrodeposition potential 35 or appropriate selection of the Cu complex precursor. 34 Copper-based materials also exhibit electrocatalytic properties towards the ORR 36 and are considered as a replacement for platinum. 37,38 A low overpotential of the ORR in alkaline media with Cu nanoparticles 39 and nanoowers 40 was reported.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] MCOs have a multi-nuclear copper complex at the reaction center and this core structure inspires us to synthesize copper-based ORR catalysts. [15][16][17][18][19][20][21][22][23][24] An intriguing example of copper-based ORR catalysts is a dinuclear copper(II) complex of 3,5-diamino-1,2,4-triazole (Cu-Hdatrz). 20,25 Cu-Hdatrz supported on carbon black shows high ORR activity in the copper-based electrocatalysts (Eonset for ORR = 0.73 V vs pH 7) 20 and its ORR activity increases with increasing pH because of the faster ORR kinetics in basic solutions revealed by in situ X-ray absorption fine structure (XAFS) spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, simple model systems, for example, two-dimensional systems, will allow us to simplify the electrode preparation process or to obtain mechanistic insights into the reaction mechanism or mass transport of oxygen or proton. 23,[27][28][29] Herein we report two-dimensional model systems to easily study the catalytic activity or oxygen transport of dinuclear copper-based ORR catalysts, which are based on Cu-Hdatrz. We have self-assembled heteroaromatic thiols (Chart 1) and then formed the copper-based ORR catalysts onto a polycrystalline gold surface.…”
Section: Introductionmentioning
confidence: 99%